2023
DOI: 10.3390/cancers15010304
|View full text |Cite
|
Sign up to set email alerts
|

Protoporphyrin IX (PpIX) Fluorescence during Meningioma Surgery: Correlations with Histological Findings and Expression of Heme Pathway Molecules

Abstract: Background: The usefulness of 5-ALA-mediated fluorescence-guided resection (FGR) in meningiomas is controversial, and information on the molecular background of fluorescence is sparse. Methods: Specimens obtained during 44 FGRs of intracranial meningiomas were analyzed for the presence of tumor tissue and fluorescence. Protein/mRNA expression of key transmembrane transporters/enzymes involved in PpIX metabolism (ABCB6, ABCG2, FECH, CPOX) were investigated using immunohistochemistry/qPCR. Results: Intraoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Postoperative tumor volume has been found to be a significant predictor of tumor recurrence in meningioma. 27 A large cohort study of 204 cases showed that 5-ALA-induced PpIX fluorescence was successful at enabling intraoperative visualization of most intracranial meningiomas as well as tumor-infiltrated bone flaps. 2 The uptake of 5-ALA into cells of the brain, both normal cortex and tumor tissue, is predicated on 5-ALA bioavailability in the microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative tumor volume has been found to be a significant predictor of tumor recurrence in meningioma. 27 A large cohort study of 204 cases showed that 5-ALA-induced PpIX fluorescence was successful at enabling intraoperative visualization of most intracranial meningiomas as well as tumor-infiltrated bone flaps. 2 The uptake of 5-ALA into cells of the brain, both normal cortex and tumor tissue, is predicated on 5-ALA bioavailability in the microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…New targeted fluorophores can bind to tumor-specific markers such as the epidermal growth factor receptor (EGFR) and other peptides [65][66][67][68]. 5-ALA has been the most exhaustively studied FGS agent for HGGs and most recently meningiomas due to its robust red fluorescence in the tumor bulk and predictive value for delineating tumor tissue versus surrounding brain parenchyma [69,70]. 5-ALA is the only FDA-approved agent for use during glioma surgery [71].…”
Section: Fluorescence-guided Neurosurgerymentioning
confidence: 99%
“…5-ALA is the only FDA-approved agent for use during glioma surgery [71]. Correlations have also been observed between fluorescence intensity and histological grading, suggesting an ability to approximate tumor grade by fluorescent signal [6,54,69,70]. Despite its promising advantages, the use of 5-ALA comes with certain drawbacks.…”
Section: Fluorescence-guided Neurosurgerymentioning
confidence: 99%